Screening of 2A peptides for polycistronic gene expression in yeast - Souza-Moreira, Tatiana M. [UNESP]; Navarrete, Clara; Chen, Xin; Zanelli, Cleslei F. [UNESP]; Valentini, Sandro R. [UNESP]; Furlan, Maysa [UNESP]; Nielsen, Jens; Krivoruchko, Anastasia (Oxford University Press (OUP), 2018)
A complexity of pathway expression in yeast compared to prokaryotes is the need for separate promoters and terminators for each gene expressed. Single transcript expression and separated protein production is possible via the use of 2A viral peptides, but detailed characterization to assess their suitability and applications is needed. The present work aimed to characterize multiple 2A peptide sequences to determine suitability for metabolic engineering applications in Saccharomyces cerevisiae. We screened 22 peptides placed between fluorescent protein sequences. Cleaving efficiency was calculated by western blot intensity of bands corresponding to the cleaved and uncleaved forms of the reporter. Three out of the 22 sequences showed high cleavage efficiency: 2A peptide from Equine rhinitis B virus (91%), Porcine teschovirus-1 (85%) and Operophtera brumata cypovirus-18 (83%). Furthermore, expression of the released protein was comparable to its monocistronic expression. As a proof-of-concept, the triterpene friedelin was successfully produced in the same yeast strain by expressing its synthase with the truncated form of HMG1 linked by the 2A peptide of ERBV-1, with production titers comparable to monocistronic expression (via separate promoters). These results suggest that these peptides could be suitable for expression and translation of multiple proteins in metabolic engineering applications in S. cerevisiae.
Keywords: 'polycistronic'; 'self-cleavage'; 'stop-carry on'; ERBV-1 2A peptide; Multi-gene expression; Saccharomyces cerevisiae; Yeast metabolic engineering